Hands-on agile software development with JIRA : design and manage software projects using Agile methodology - Harned, David (Birmingham, UK : Packt Publishing, 2018)
Plan, track, and release great software Key Features Learn to create reports and dashboard for effective project management Implement your development strategy in JIRA. Practices to help you manage the issues in the development team Book Description As teams scale in size, project management can get very complicated. One of the best tools to deal with this kind of problem is JIRA. This book will start by organizing your project requirements and the principles of Agile development to get you started. You will then be introduced to set up a JIRA account and the JIRA ecosystem to help you implement a dashboard for your team's work and issues. You will learn how to manage any issues and bugs that might emerge in the development stage. Going ahead, the book will help you build reports and use them to plan the releases based on the study of the reports. Towards the end, you will come across working with the gathered data and create a dashboard that helps you track the project's development. What you will learn Create your first project (and manage existing projects) in JIRA Manage your board view and backlogs in JIRA Run a Scrum Sprint project in JIRA Create reports (including topic-based reports) Forecast using versions Search for issues with JIRA Query Language (JQL) Execute bulk changes to issues Create custom filters, dashboards, and widgets Create epics, stories, bugs, and tasks Who this book is for This book is for administrators who wants to apply the Agile approach to managing the issues, bugs, and releases in their software development projects using JIRA.
Cover -- Title Page -- Copyright and Credits -- Dedication -- Packt Upsell -- Contributor -- Table of Contents -- Preface -- Chapter 1: Getting Started with Creating Projects -- Introduction to JIRA -- What is JIRA? -- Creating an account with Atlassian -- How JIRA uses projects to keep work organized -- Project management -- Summary of project settings -- How to set up a project using a scheme, screens, workflows, and permissions -- Screens -- Workflows -- Permissions -- Notifications -- Summary -- Chapter 2: Managing Work Items -- Introducing epics, stories, bugs, and tasks -- Creating epics, stories, bugs, and tasks -- Issue type attributes and adding and removing them -- Managing items in the backlog -- Creating and configuring our board -- Summary -- Chapter 3: Running Your Project in JIRA -- Creating and starting a sprint -- The daily scrum -- Smaller stories and tasks -- Closing the sprint - the sprint report -- Summary -- Chapter 4: Working with Reports -- Versions and releases -- Burndown reports -- Burndown example one -- Burndown example two -- Burndown report -- Sprint reports -- Velocity charts -- Velocity charts - an example -- Release and epic burndowns -- Release burndown - an example -- Version and epic reports -- Version report - an example -- Summary -- Chapter 5: Issue Searching and Filtering -- Issue searching using JQL -- Simple and advanced JQL editors in JIRA -- Saving and managing filters -- Executing bulk changes -- Creating new boards from saved filters -- Summary -- Chapter 6: Dashboards and Widgets -- Creating and managing a dashboard -- Adding gadgets to our dashboard -- Sharing a dashboard -- Summary -- Other Books You May Enjoy -- Index.
Description based on online resource; title from title page (Safari, viewed September 5, 2018).
eBooks on EBSCOhost
Keywords: JIRA (Computer file); JIRA (Computer file); Agile software development; Computer software -- Development; Issues management -- Computer programs; Project management -- Computer programs; Méthodes agiles (Développement de logiciels); Gestion par problèmes -- Logiciels; Agile software development; Computer software -- Development; Project management -- Computer programs